Digitalization of the Economy: a Challenge to Higher Education and Ways to Overcome - E. N. Sirota (Модернизация, инновация, развитие, 2019)
Purpose: the purpose of this article is to study the challenges of higher education in the digitalization of the economy and ways to overcome them. Achieving the goal is provided by identifying the system attributes of the digital economy, the gaps between the needs of the digital economy and the possibilities of providing them with the current education system, the problems that arise and the possible directions for solving them in connection with the tasks of innovative development of Russia. Methods: the study is based on a systematic approach, including a functional-structural method, multi-level and hierarchical in combination with the historical-dialectical method. These methods make possible to identify the occurrence of qualitative transformations of the system from reaching quantitative boundaries, a change in the main opposing forces and the nature of their interaction in the system, the direction of negation of the previous stage of the system and the fundamental characteristic of its new state. The combination of these approaches predetermined the choice of specific research methods: phenomenological, comparative, inductive. Results: the fundamental difference between the digital economy as the fifth technological paradigm and all previous ones have been formulated in the context of biological and socio-cultural evolution. The connections of digitalization with innovative development, technological and social singularity were shown. The system challenge of digital economy to the education, that includes the functional-structural, psychological, pedagogical and institutional ones, has been revealed and disclosed. Directions of interdisciplinary research are proposed that allow answering these challenges, as well as some methodological innovations that allow to accelerate and to increase the efficiency of the learning process, in particular, programmable learning applications that self-adjust using individual dynamic cognitive profiles of students formed in the learning process. Conclusions and Relevance: the functional and structural challenge to the education system creates significantly complicated requirements for the qualitative characteristics of human capital. They are manifested in an increase in the volume of relevant competencies and the speed of their obsolescence, shift of emphasis from standard unidisciplinary to inter- and multidisciplinary problem tasks, in new relations between the depth of professional knowledge and the breadth of general cultural orientation. The incomplete readiness of cognitive psychology and pedagogy to bridge the gap between the explosive growth in the volume of relevant knowledge and the limited speed of its development forms the content of the psychological and pedagogical challenge, and the organizational and economic disconnection of education and business exacerbates the challenge with the institutional component. An adequate response to challenges is possible through the own efforts of the educational system to individualize the learning process using artificial intelligence systems, focused on maximizing the cognitive and psychological characteristics of the student. An interdisciplinary search for safe borders, technical means and psychological tools to intensify the educational process, which allow us to give a worthy answer to these challenges. This direction can become the basis of an interdisciplinary discussion about the ways in which society responds to the challenges of digitalization, as well as for applied pedagogical developments.